2016
DOI: 10.1016/j.jjcc.2015.06.014
|View full text |Cite
|
Sign up to set email alerts
|

An increase in the coronary calcification score is associated with an increased risk of heart failure in patients without a history of coronary artery disease

Abstract: Severe CAC is an independent determinant of high NT-proBNP levels and a predictor of admission for HF in a population without a history of CAD or HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…In our study, we showed that the association of CAC progression and HF remained statistically significant, even after excluding all participants with CHD. Our result is in agreement with a few previous studies that evaluated the association between baseline CAC and HF …”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In our study, we showed that the association of CAC progression and HF remained statistically significant, even after excluding all participants with CHD. Our result is in agreement with a few previous studies that evaluated the association between baseline CAC and HF …”
Section: Discussionsupporting
confidence: 94%
“…Our result is in agreement with a few previous studies that evaluated the association between baseline CAC and HF. 14,15,17 Kalsch et al in the Heinz Nixdorf Recall Study has shown a significant association between CAC and history of HF in a univariate cross-sectional analysis. 14 This association became statistically insignificant after adjusting for traditional cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations